P86 Are process evaluation measures related to intervention outcomes in the pace-up primary care pedometer-based walking trial?. (2nd September 2017) - Furness, C; Howard, E; Limb, E; Cook, DG; Kerry, S; Wahlich, C; Victor, C; Ekeland, U; Iiffe, S; Ussher, M; Ussher, M; Whincup, P; et al.
Abstract : Background: PACE-UP trial results demonstrated positive effects of a pedometer-based walking intervention on objective physical activity (PA) outcomes at 3 and 12 months in 45–75 year old primary care patients, in both postal and nurse-supported trial arms compared to controls. We explored associations between intervention implementation measures and change in PA outcomes. Methods: In accordance with the MRC guidance and framework (2014), the methods were selected through a key function model. Three quantitative aspects of the process evaluation relating directly to PA outcomes at 12 months were identified to assess intervention implementation: nurse session attendance (dose); PA diary completion (fidelity); and pedometer use (fidelity). These were considered as independent variables in the multi-level models estimating the effectiveness of the intervention on PA outcomes (changes in step-counts and time in moderate-to-vigorous PA (MVPA) levels in ≥10 min bouts). Results: Dose participants attending all 3 nurse sessions increased their step-count at 3 months by 961 steps more than those attending 0–2 sessions (95% CI 401–1520, p=0.001). Minutes of MVPA were also significantly increased by 64 (36, 92) at 3 months and by 28 (1, 54) at 12 months. Fidelity: both postal and nurse groups showed strong positive associations of diary return on step-count and minutes of MVPA at 3 months compared with those who didn't return the diary: postal steps 1458 (854, 20161), nurse steps 873 (190, 1555), postal MVPA 64 (33, 94), nurse MVPA 47 (17, 75). These differences had decreased by 12 months, and only the postal group effects remained statistically significant: steps 1114 (538, 1689), MVPA 47 (17, 75). Regular pedometer use in the postal group was associated with higher step counts at 3 and 12 months: 1029 (383, 1675) and 606 (22, 1990) respectively. Regular pedometer use was not associated with PA outcomes in the nurse group. Discussion: Process evaluation measures showed significant associations with most PA outcomes at 3 and 12 months. These were stronger for the postal than the nurse group for diary and pedometer use. We cannot infer causality from these results, but the strong associations between nurse appointments, diary return, pedometer use and PA outcomes suggests that they were important factors in enabling the trial changes observed. We have shown the MRC framework to be an effective tool for process evaluation of intervention implementation.